Integrasi Pendekatan Balaghah dan Stilistika dalam Analisis Ayat-Ayat Tematik al-Quran : Analisis Gaya Bahasa Ayat-Ayat Takwa - Muhamad Ridwan, Rayhan; Satria Wiwaha, Rizzaldy; Azhar, Ruly Syaepul; Wiwaha, Rizzaldy Satria (Ta'limi | Journal of Arabic Education and Arabic Studies, 2026)
This study explores the integration of stylistic and balaghah (Arabic rhetoric) approaches in analyzing the verses of the Qur'an that have the theme of taqwa. Using qualitative methods through literature study, this study aims to reveal how linguistic aesthetics and rhetorical devices strengthen the spiritual and ethical dimensions of the concept of taqwa as conveyed in the Qur'an. The balaghah approach examines the beauty of expression through the elements of bayan, ma'ani, and badi' that frame the divine message with persuasive clarity while the stylistic analysis highlights lexical choices, syntactic structures, and rhythmic patterns that evoke emotional and reflective responses. The integration of these two approaches shows that taqwa is not merely a theological doctrine, but a profound moral and spiritual principle, communicated through the tiered language art of the Qur'an. The findings of this study indicate that this kind of integrative approach offers a richer and more multidimensional understanding of the Qur'anic discourse, while also confirming its unique position as a text of guidance full of beauty and rhetorical depth.